A brief history of Christianity - Gascoigne, Bamber (Robinson, 2003)
This volume tells the story of Christianity through the individual men and women who shaped it. It is a story of colossal undertakings and spectacular successes as well as ferocious intolerance, greed and bloodshed. Bamber Gascoigne traces a clear path through a complicated history, exploring the motives, the passions, the fears and the achievements of the Christians. His approach is objective and he writes in a conversational style, focusing on moments of significant detail and a vast and varied cast of characters.